Digital disorientation and place. (June 2021) - Relph, Edward
Digital technologies affect experiences of place in ways that are disorienting because they overwhelm us with information and images, bring into question what is real and what is fake, confuse real and virtual reality, and exacerbate extreme views about who belongs where. The consequences of this 'digital disorientation' might seem to be experienced as unremarkable and benign. However, it is becoming increasingly clear that these consequences include a digitally poisoned sense of place based on exclusionary attitudes paradoxically fostered in the echo chambers of non-place communities. Resisting this and its political manifestations will require finding ways to promote an open and inclusive digital sense of place that is necessarily grounded in the actual places of everyday life; that understands that digitally these actual places are both permeated by and reach out into distant times and places; and that embraces rather than denies difference.